Elite athlete immunology: importance of nutrition - Gleeson, M.; Bishop, N. C. (International Journal of Sports Medicine, 2000)
Immunosuppression in athletes involved in heavy training is undoubtedly multifactorial in origin. Training and competitive surroundings may increase the athlete's exposure to pathogens and provide optimal conditions for pathogen transmission. Heavy prolonged exertion is associated with numerous hormonal and biochemical changes, many of which potentially have detrimental effects on immune function. Furthermore, improper nutrition can compound the negative influence of heavy exertion on immunocompetence. An athlete exercising in a carbohydrate-depleted state experiences larger increases in circulating stress hormones and a greater perturbation of several immune function indices. The poor nutritional status of some athletes may predispose them to immunosuppression. For example, dietary deficiencies of protein and specific micronutrients have long been associated with immune dysfunction. An adequate intake of iron, zinc and B vitamins is particularly important but the dangers of over-supplementation should also be emphasized; many micronutrients given in quantities beyond a certain threshold will in fact reduce immune responses and may have other toxic effects that are detrimental to health. Although it is impossible to counter the effects of all of the factors that contribute to exercise-induced immunosuppression, it has been shown to be possible to minimize the effects of many factors. Athletes can help themselves by eating a well-balanced diet that includes adequate protein and carbohydrate, sufficient to meet their energy requirements. This will ensure a more than adequate intake of trace elements without the need for special supplements. Consuming carbohydrate (but not glutamine) during exercise attenuates rises in stress hormones such as cortisol and appears to limit the degree of exercise-induced immunosuppression. By adopting sound nutritional practice, reducing other life stresses, maintaining good hygiene, obtaining adequate rest and spacing prolonged training sessions and competition as far apart as possible, athletes can reduce their risk of infection.